Taxonomy of Polyporus Sensu lato and Related Genera (basidiomycota) from Santa Maria, Southern Brazil - Coelho, Gilberto; Silveira, Rosa Mara Borges da (Ciência e Natura, 2014)
Polyporus has traditionally been treated at a generic status, but currently, it is considered as a polyphyletic assemblage of some poroid stipitate genera and morphological groups of fungi to be better understood. Ten species of Polyporus sensu lato and one species of Echinochaete (Polyporales, Basidiomycota) were identified to the region of Santa Maria, Rio Grande do Sul State, southern Brazil. Fresh basidiomes were collected and analyzed in order to present their illustrated morphological redescriptions. Polyporus subpurpurascens is recorded for the first time from Brazil.